Al-Kindi Thinking: Harmonization of Islam and Philosophy - Rieski Triyanto, Jefri (Risâlah Jurnal Pendidikan dan Studi Islam, 2025)
The purposes of this study are as follows: (1) to analyze and describe Al-Kindi's philosophers about philosophy; (2) to analyse and to describe the philosopher of one of the Islamic figures named Al-Kindi in an attempt to harmonize his thinking between philosophies and Islamic religions. The research method used in this research uses historical research with an approach to the study of literature. The result of this study is the study of philosophy and religion carried out by Al-Kindi realized with the existence of reconciliation to prove that between philosophers and religions equally constitutes a science of truth and there is no difference between the two. Therefore, the role of the Al-Kindi figure is very important as the first philosopher who came from the Muslim community. KEY WORDS: Thought; Al-Kindi; Islam; Philosophy